Análisis del contenido del programa “Primera cita” del canal de youtube ingobernables ec - Nuñez Barandica, Jeniffer Melissa (2023)
The present case study is based on the analysis of the content of the program “Primera Cita” and its influence on society, it is a program that was born in the city of Guayaquil in the province of Guayas, being a program transmitted by the YouTube platform which It can be seen in several countries, thus having an international reach. The journalist who teaches this program is dedicated to informing, entertaining and addressing various topics including political, educational, and useful and interesting information. Therefore, the impact and contribution that the content of this program has on society will be observed and analyzed in this document, including the opinion of experts in the journalistic field and at the same time of its audience. The analytical method was used to achieve the stated objectives, a community survey and an interview with a communication graduate were implemented as a tool, which resulted in the positive contribution that the “first date” program has in society.